The Knowledge of Hospitality in the Redemption of Christ - Christar A. Rumbay (Sekolah Tinggi Teologi Real Batam, 2019)
Christology testifies notions in several Christian dogmatic. The ethics of the crucifixion of Christ, however, receive less attention. Consequently, the intention to share the knowledge of Christ in the cross being limited as it occupies theological reflection intensively. This article attempts to delve into the unseen ethics nature of the event of redemption, hospitality. Its characters are portrayed in several events in the scripture but rarely evaluated from the eye of Christology, especially speaking, the redemption of Christ in the cross. The intention of this treatise is; to explore the nature of hospitality in the display of cross that could be offered a new perspective to the theological environment and help the reader to see unseen knowledge.